The diet and environment of mammoths in North-East Russia reconstructed from the contents of their feces. (25th June 2016) - Kirillova, Irina V.; Argant, J.; Lapteva, E.G.; Korona, O.M.; van der Plicht, J.; Zinovyev, E.V.; Kotov, А.А.; Chernova, O.F.; Fadeeva, Е.О.; Baturina, O.A.; Kabilov, M.R.; Shidlovskiy, F.K.; et al.
Abstract: Mammoth feces from northern Yakutia and western Chukotka were investigated in a multidisciplinary study. Radiocarbon dating of the Yakutian mammoth dung yielded ca 42 ka BP and the age of the feces from Chukotka is older than 45 ka BP. The two sites are located about 15, 000 km from each other and have a different geological setting. Most plant remains in the dung of both mammoths were grasses and sedges, with some other herbs and dwarf shrubs in addition. The pastures were situated in varying treeless shrubby landscapes: herb–grass associations of meadows, wormwood and shrub biotopes on slopes, in valleys and at watersheds. Besides plant remains and hairs of large herbivore mammals, the feces also contained feathers of Anseriformes, fragments of beetles and flies, ephippia of Cladocera, diatoms, remains of testate amoebae and ascospores of coprophilous fungi from pasture cenoses.